PENYULUHAN KESANTUNAN BERBAHASA DI SMA AGAPE HALMAHERA BARAT - Duwila, Ety; Rauf, Ramis; Ulya, Afriani (Universitas Teknokrat Indonesia, 2023)
The era of digitalization opens spaces for anyone to express themselves, primarily through virtual spaces such as Facebook, YouTube, Instagram, TikTok, and Twitter. The implication is that cultural and moral degradation is caused by foreign cultural intervention through content uploaded on social media, especially regarding impoliteness in language. Social media has several forms of language impoliteness, such as swearing, threats, insults, and hoax news. This form of language impoliteness in social media leads to defamation and hate speech. Defamation and hate speech violate Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE). The problem of defamation and hate speech is one of the vital national issues that must be resolved. Therefore, as a lecturer responsible for the tri dharma of higher education, the authors plan to conduct community service titled